دراسة تحليلية لأداء الأفراد العاملين في المصارف العامة في محافظة اللاذقية والعوامل المؤثرة فيه - حرب بيان; ميا علي; ناصر سومرأديب (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يهدف هذا البحث إلى دراسة العوامل المؤثرة في أداء الأفراد العاملين في المصارف العامة، نظراً لما للأداء الفردي من أثر مباشر على الأداء الكلي للمصارف من جهة، والدور الهام الذي تلعبه المصارف في الحياة الاقتصادية والاجتماعية من جهة ثانية، حيث تأكد هذا الدور عبر ما تقدمه المصارف من خدمات متنوعة أصبحت واحدة من أهم دعائم تمويل التنمية. وتضمن البحث: دراسة نظرية. حول الأداء الفردي والعوامل المؤثرة فيه. دراسة ميدانية. للأداء الفردي في المصارف العامة، تم من خلالها تجميع البيانات اللازمة لخدمة أغراض البحث. وأشار البحث إلى عدة توصيات أهمها: تحسين ظروف العمل ضمن المصارف المدروسة. تحسين نظام الحوافز. زيادة عدد الأفراد العاملين بما يساعد على السرعة في العمل. This study aims to study the factors affecting individuals working for public banks in Lattakia, since, on the one hand, individual performance has a direct influence on the bank’s overall performance, and that banks play an important role in economic and social life, on the other. So, this role is confirmed by the various services offered by these banks, which make them the basic pillars of financing growth. The research includes: - A theoretical study of individual performance and the factors affecting .it - A field study of individual performance in public banks from which data are collected to serve research purposes. This research proposes a number of recommendations: - Improvement of incentive system and workplace conditions within the banks - Increasing the number of employees to help speed up work..